Energetic and exergetic metrics of a cargo aircraft turboprop propulsion system by using regression method for dynamic flight - Kirmizi, Mehmet; Aygun, Hakan; Turan, Onder (Pergamon-Elsevier Science Ltd, 2024)
Nowadays, the development of aviation in line with sustainability goals is one of the current challenges. Being a source of environmental impact, aero-engines have been the main research and design object for achieving these aims. In this study, thermodynamic analysis involving exergy and sustainability computations is performed at different flight conditions where Mach varies between 0 and 0.7 and altitude changes between 0 and 7.7 km. Based on this analysis, modeling exergy parameters for each component are carried out with multiple regression approach. The exergy efficiency of turboprop engine at dynamic flight conditions varies between 15% and 25.9% whereas it is measured between 76 and 77% for the combustor and between 93 and 99% for gas turbine. Moreover, exergy destruction of the turboprop engine changes between 2.15 MW and 7.55 MW. Exergetic improvement potential rate (IPR) of the combustor resides between 0.4 MW and 1.21 MW throughout flight conditions whereas it is found at orders of 0.1 MW or less for other components. On the other hand, linear and quadratic modelings are performed for several parameters of turboprop engine components including exergy efficiency, exergy destruction and IPR under dynamic flight conditions. The determination coefficient (R2) of the models changes between 0.69 and 0.98 in linear modeling, whereas R2 in quadratic modeling improves to 0.97 and 0.99 ranges. It is thought that component-based modeling by considering different flight conditions could contribute to determining points where component efficiency is the highest.
Keywords: Exergy; Turboprop; Regression; Sustainability